Keragaan Beberapa Genotipe Tomat (Lycopersicum esculentum mill.) di Dataran Rendah - Idham, Muhammad Muas; ', Ardian; ', Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The study was conducted from October to March 2013 at Agriculture faculty, University of Riau . The experimental design used was Randomized  Block Design (RBD), consisting of 6 treatments and 3 replications, which is total 18 experimental units. Data were analyzed using analysis of variance and tested further by Least Significant Difference (LSD) level of 5 %. The parameters measured were plant height (cm), stem diameter (cm), days to flowering days after sowing (DAS), days to harvesting after sowing (DAS), fruit length (cm), fruit diameter (cm), number of fruit space, fruit flesh thickness (mm), number of seeds per gram, number of fruits per plant, weight per fruit (g) and weight of fruit per plant (g). The results show variability genotypes tested and the results are different in each genotype . Tomato strains tested have the ability to grow and yield better than varieties Ratna and Karina as a comparison . IPB T43-6-8 and IPB T34-7-7 is a strain with high yield . IPB T60- 2-6  and IPB T65-9-2012 is a strain that has a moderate yield, as well as Ratna and Karina is a variety which has the lowest yield. Key words : Lycopersicum esculentum, low plain